Development Media LUNTAR (Ludo Bangun Datar ) is Problem Based to Improve Critical Thinking Skills Fourth Grade Elementary School Students - Firda Choirun Nisa'; Cindya Alfi; Mohamad Fatih (Indonesian Journal of Primary Education, 2023)
The aim of developing problem-based LUNTAR (Ludo Bangun Datar) media is to further improve critical thinking skills in fourth grade elementary school students. This research uses research and development ( RD) methods. The model used by researchers is the ADDIE model which consists of 5 steps, namely analysis , design , development , implementation and evaluation . The instruments in this research used observation, interviews, tests and questionnaires. Data collection techniques used include observation, interviews, validation of material experts and media experts as well as tests to improve critical thinking skills. The data analysis technique used is descriptive analysis technique quantitative. The research results in this study can be seen from the average results of media experts for problem-based LUNTAR media getting 3.8 which is declared "feasible" and the material expert assessment gets 4.5 which is declared "very feasible". Based on the effectiveness of the media, teachers' responses received an average of 4.8 which was declared "very effective" while the pre-test and post-test results of class IV students using the N-Gain test received an average of 0.92 in the "high" category. Based on the results of this research, it can be concluded that research and development of problem-based LUNTAR media can improve the critical thinking skills of fourth grade elementary school students.